Study regarding the vegetable market in Romania in the period 2015-2019 - Diana Creţu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The paper presents the vegetable market in the period 2015-2019 in Romania, highlighting aspects such as: cultivated area of vegetables, vegetable production, price dynamics, average annual consumption, domestic and foreign trade. The fruit and vegetable market is one of the most important sectors of the world economy, so in this paper I proposed a five-year analysis to see the evolution of this sector in Romania. The research method used in the study is statistical processing and economic analysis of existing data for the period 2015-2019 on specialized sites such as the National Institute of Statistics (NIS), Eurostat, FAO, Ministry of Agriculture and Rural Development (MADR) but and other specialty materials.
Keywords: Q11; Q13; L11; 330; vegetable market; consumption; price dynamics